PENGARUH DUKUNGAN KELUARGA TERHADAP PENGAWASAN DIET PADA PASIEN DIABETES MELITUS - Lian, Muhammad; Rambe, Ira Purnama Sari; Nurhayati, Evalatifah; Lubis, Lisnawati; Simanjuntak, Rokkianto (Universitas Murni Teguh, 2024)
Diabetes, often known as diabetes mellitus, is a metabolic disease that develops when a person's blood sugar levels rise over normal ranges. Abnormal glucose metabolism in response to high absolute and relative insulin levels is the etiology of diabetes, or DM. For DM patients, the involvement and support of family play a vital part in the efficacy of media treatment. Any counsel or words of encouragement that the group offers to sick individuals or other members who are experiencing health issues is considered family support. In addition to functional ability, psychological well-being, social health, and well-being, illness and its treatment can impact the health and social well-being of those with DM. The study's goal was to look over how family support affected the dietary monitoring of RSU Bina Kasih Medan patients with diabetes mellitus. This study approach employs a cross-sectional design. Primary data, or information gathered through in-person interviews and the distribution of questionnaires, is used in this data collection. Research findings show a p value <0.05. There is an influence of emotional support on diet supervision with p value (0.038). There is an influence of family information support on dietary supervision with p value (0.010). There is an influence of family instrumental support on dietary supervision with a p value (0.04) and there is an influence of family assessment support on dietary supervision with a p value (0.03). It is evident that family assistance is essential to helping diabetes mellitus patients monitor their diets over the course of their recovery and treatment. Abstrak Diabetes merupakan penyakit metabolik yang berkembang pada individu yang kadar gula darahnya berada dalam kisaran abnormal. Metabolisme glukosa yang tidak normal yang disebabkan oleh peningkatan kadar insulin absolut dan relatif yang merupakan penyebab utama diabetes, atau DM. Keterlibatan dan dukungan keluarga pasien memiliki peran utama pada keberhasilan terapi yang dijalani. Dukungan keluarga mencakup semua bentuk nasihat atau kata-kata penyemangat yang diberikan keluarga kepada anggota yang sakit atau menderita berbagai kondisi medis. Selain kemampuan fungsional, kesejahteraan psikologis, kesehatan sosial, dan kesejahteraan, kesehatan dan kesejahteraan sosial penderita DM mungkin dipengaruhi oleh penyakit dan pengobatannya. Tujuan penelitian ini mengamati dampak dukungan keluarga terhadap pengawasan diet pada pasien diabetes di RS Bina Kasih. Desain cross-sectional digunakan dalam metodologi penelitian ini. Data primer, atau informasi yang dikumpulkan melalui wawancara langsung dan penyebaran kuesioner digunakan dalam pengumpulan data ini. Temuan penelitian menunjukkan nilai p value < 0,05. Ada pengaruh dukungan emosional terhadap pengawasan diet dengan p value (0,038). Ada pengaruh dukungan informasi keluarga terhadap pengawasan diet dengan p value (0,010). Ada pengaruh dukungan instumental keluarga terhadap pengawasan diet dengan p value (0,04) dan ada pengaruh dukungan penilaian keluarga terhadap pengawasan diet dengan p value (0,03). Dapat disimpulkan bahwa Dukungan keluarga berperan penting dalam membantu individu penderita diabetes melitus mengatur pola makannya selama fase penyembuhan dan terapi.